C‐reactive protein trajectory in the first 48 hours predicts the need for intervention in conservative management of acute diverticulitis. Issue 10 (4th August 2020) - Ahmadi, Nima; Ravindran, Praveen; Kim, Taejun; Ayoubi, Salah E.; Byrne, Christopher M.; Young, Christopher J.
Abstract: Background: C‐reactive protein (CRP) is a useful marker for monitoring response to treatment in sepsis. The aim of this study was to examine the use of CRP trajectory in predicting the need for intervention in conservatively managed patients with acute diverticulitis (AD). Methods: A retrospective review of patients with AD who were managed conservatively was performed. They were divided into four groups based on CRP relative to the median at day 0 and 2: 'Low rise' (levels below median at day 0 and 2), 'High rise' (levels above median at day 0 and 2), 'Rapid rise' (levels below median at day 0 but above median at day 2) and 'Decline' (levels above median at day 0 but below median at day 2). Results: Intervention was required in 64 of 456 (14%) with 30 (48%) of these performed after day 2 of admission. There were 150 patients (54%) in the 'Low rise', 76 (27%) in the 'Decline', 26 patients (9%) in the 'Rapid rise' and 25 patients (9%) in the 'High rise' groups. Within these groups 5%, 8%, 19% and 32% of patients required intervention ( P = 0.001). On multivariate analysis, patients with a pelvic abscess were more likely to need intervention (odds ratio 19.1 (confidence interval 6.2–59.4), P < 0.0001). Conclusion: The CRP trajectory during the initial 48 h of admission can predict the need for intervention in AD patients being managed conservatively. Patients with a 'Rapid rise' or 'High rise' in CRP from day 0 to 2 are more likely to need intervention. Abstract : This paper demonstrates the utility of a dynamic assessment of C‐reactive protein in predicting the failure of conservative management of acute diverticulitis in patients not needing immediate surgery or radiological intervention. If the C‐reactive protein is persistently high or is rising in the first 2 days of admission, then there is a higher risk of intervention during the hospital admission. This is the first time such a dynamic assessment is performed in patients with acute diverticulitis.